A comprehensive model and its optimal dispatch of an integrated electrical-thermal system with multiple heat sources. (15th December 2022) - Dai, Yuanhang; Hao, Junhong; Wang, Xingce; Chen, Lei; Chen, Qun; Du, Xiaoze
Abstract: As essential parts of the combined heat supply network with multiple heat sources, the electrical-heating and heat storage technology can simultaneously achieve the goal of clean heating and renewable energy accommodation. The paper introduces the integrated electrical-thermal system with multiple heat sources that consist of combined heat and power (CHP), coal-fired boiler (CB), and electrical boiler (EB) with thermal energy storage (TES). Considering the integration of electrical and thermal networks, we construct a comprehensive model that includes the electrical energy transmission and the overall heat transfer and storage processes based on the heat current method. Based on the comprehensive model, the optimal dispatch of the integrated system is discussed, and an iteration solving method is proposed, which can achieve acceptable convergence and solving efficiency. The simulation results show the combined operation of multiple heat sources has higher system operation efficiency but not necessarily a higher utilization rate of renewable energy. In the test system the combined operation of CHP and coal-fired boiler can reduce the coal consumption of the system by 2%. However, the wind utilization of the system decreases by 4.17%. Moreover, the introduction of an electrical boiler with a TES device can improve the system's flexibility and reduce wind curtailment, wherein the test system is 12.11% more wind consumption. Further, the heat load level can affect the operation efficiency of CHP, the combined operation of multiple heat sources can achieve the balance between reducing coal consumption and increasing renewable energy power generation. Highlights: Proposed multiple heating sources for heating in the integrated electric and thermal system. Introduced the heat current method for the comprehensive modeling of integrated energy system. Coordinatively analyzed the heat transfer process and power transmission of system modeling. Provided a new coordination dispatch method for optimal scheduling of power and heat generation.